Use of Reticulated Hyaluronic Acid Alone or Associated With Ozone Gas in the Treatment of Osteoarthritis Due to Hip Dysplasia in Dogs - Silva Júnior, José I. S. [UNESP]; Rahal, Sheila C. [UNESP]; Santos, Ivan F. C. [UNESP]; Martins, David J. C. [UNESP]; Michelon, Fernanda [UNESP]; Mamprim, Maria J. [UNESP]; Tomacheuski, Rubia M. [UNESP]; Correia, Luiz E. C. S. [UNESP] (Frontiers, 2020)
This study aimed to evaluate reticulated hyaluronic acid alone or associated with ozone gas in the treatment of osteoarthritis due to hip dysplasia in dogs. Fourteen client-owned dogs were randomly assigned into two groups: Group 1—single intra-articular injection of hyaluronic acid; Group 2—single intra-articular infiltration injection of hyaluronic acid associated with ozone gas. Each hip joint received an average of 0.75 mL of reticulated hyaluronic acid ultrasound-guided. Ozone gas at a dose of 45 μg/mL was incorporated into hyaluronic acid by insufflation. Dogs were evaluated for body condition scoring, orthopedic examination and radiographic scores of the hip joints, goniometric measurements of the hip joints, visual gait score, and kinetic analysis. The evaluations were conducted immediately before treatments (M0), and at days 30 (M1), 60 (M2), and 90 (M3) after treatments. There were no significant differences in body mass and body condition scoring (5-point scale) in each group in all evaluation moments. The scores of orthopedic examination of the hip joints showed statistical differences in each group between moments (M0 > M3), but differences were not observed between groups. No statistical differences were found for radiographic scores in each group between moments, but differences were observed between groups immediately prior to treatments (G1 > G2) and 90 (G1 > G2) after treatments. Goniometric measurements of hip flexion and extension showed no significant differences in each group between moments or between groups. No statistical differences between groups were found concerning the lameness score. There were significant differences for lameness score among moments in Group 1, being M0 > M2 and M0 > M3, and Group 2 in which M0 > M1, M0 > M2, and M0 > M3. The mean percentage of change of PVF and VI between M3 and M0 in Group 1 was almost null and in Group 2 was positive, being 31.1 ± 29.4 and 10.6 ± 25.4, respectively. In conclusion, the intra-articular viscosupplementation alone or associated with ozone gas allowed improvement of lameness scores and orthopedic examination score. In Group 2 the association of ozone gas had better results on kinetic analysis.
Keywords: articular degeneration; dysplasia; pain; treatment; viscosupplementation